Uji Aktivitas Antioksidan Ekstrak Etanol Kulit Alpukat (Persea americana Mill.) terhadap Peredaman DPPH - Angga; Amelia Siyanti; Nurul Fitriani (Proceeding of Mulawarman Pharmaceuticals Conferences, 2019)
Avocado peel is contains chemical compound of alkaloid as antioxidant. So, has been research is to determine the antioxidant activity of ethanol extract avocado peel (Persea americana Mill.) inhibition of DPPH radical (2,2-diphenyl-1-picrylhydrazyl). The extraction method used maceration with 96% ethanol solvent. The ethanol extract avocado peel with variant concentrations are 50 ppm, 75 ppm, 100 ppm, 125 ppm, 150 ppm and ascorbic acid standard as a positive control with variant concentrations are 2 ppm, 4 ppm, 6 ppm, 8 ppm, 10 ppm. Antioxidant activity inhibit DPPH (2,2-diphenyl-1-picrylhydrazyl) radical reduction was measured using Uv-Vis spectrophotometry. The results of antioxidant activity was obtained at IC50 (inhibition concentration) from the ethanol extract avocado is 137.34 ppm and ascorbic acid is 13.18 ppm. The results of ethanol extract avocado peel has moderate antioxidant activity.